ALBINISM AND USABILITY OF SOFTWARE FOR COMPUTER-BASED TESTING IN KOGI STATE UNIVERSITY: IS THERE NEED FOR ASSISTIVE TECHNOLOGY? - Okon, Emmanuel O.; Baba, Pauline Ann; Agbogun, Joshua B. (International Journal For Research In Business, Management And Accounting, 2017)
This research paper is an evaluation of usability of software for computer-based testing in Kogi State University by students and candidates with albinism. A qualitative research design was employed for the study because the intent was to elicit information from the respondents. The responses show that the interaction of the user (students with albinism) with computer through specific interfaces during the course of computer-based testing was reasonably satisfactory. However, the software used does not give warning sounds (auditory displays) to indicate that something needs attention during CBT. From the response of 88.7% of the respondents, it is obvious that the software effectively monitors time during CBT examination. Disappointingly, there was no time extension placed on the software/program for student with albinism to complete the test as reported by 91.9% of respondents. All the respondents were of the opinion that assistive technologies should be adopted during CBT examination for people with low vision in KSU. Therefore, this paper recommends that the software designers for CBT in KSU should take into consideration more graphics interfaces, auditory displays, time extension for students with low vision and various assistive technologies that students might use. The University management should make effort at providing assistive technologies to compensate for low vision students. This will help advance quality and equity in education by providing fair and valid assessment for all students and candidates including those with albinism.